الرؤية الاخراجية للقيم الفنية والتربية في عروض المسرح المدرسي في محافظة ديالى - سھاد رشید علي (مجلة الفتح للبحوث التربوية والنفسية, 2023)
الملخص للمسرح دور فعال في إرساء المفاھیم الفنیة والتربویة وھو یعتبر من أدوات التوصیل الفكري والفني بطریقة ھادفة لانھ اداة مثیرة لملكة الخیال عند الطفل وبطریقة مرنة وھنا تكمن مشكلة البحث وھي الرؤیة الإخراجیة للقیم الفنیة والتربویة ، والیات ایصال القیم التربویة وتعریف الطفل بالفن وتنمیة الذائقة الفنیة لدیھ وعلى ھذا الأساس بني ھذا البحث الذي یتضمن اربعة فصول . تناول الفصل الاول منھ مشكلة البحث التي تتخلص بالتساؤل التالي : ما ھي الرؤیة الإخراجیة للقیم الفنیة والتربویة في عروض المسرح المدرسي ؟ وھل حاول المخرج تقدیمھا بالشكل الذي یتلائم مع مستواھم الفكري والعلمي ام اضعف في ذلك ؟ كما حددت الباحثة ھدف البحث وھو التعرف على الرؤیة الاخراجیة للقیم الفنیة والتربویة في عروض المسرح المدرسي واھمیتھا بالنسبة للتلامیذ . ثم حددت العروض في محافظة دیالى عام ٢٠١٢ ومن ثم انتھى الفصل بتحدید المصطلحات التي وردت في عنوان البحث . اما الفصل الثاني فقد تضمن مبحثین الاول منھا تناول الاخراج والثاني تناول المسرح المدرسي واثره في التربیة والتعلیم واخیرا الدراسات السابقة ومؤشرات الاطار النظري . وقد عني الفصل الثالث لعرض اجراءات البحث ضمن وصف لمجتمع البحث الذي تضمن مجموع عروض مسرحیة للمرحلة الابتدائیة في محافظة دیالى وعینات البحث التي كان عددھا (٢ (عینة وطریقة التحلیل لھذه العروض (التحلیل الوصفي) وقد اعتمدت الباحثة مؤشرات الاطار النظري في تحلیل عینات البحث . وفي الفصل الرابع خرجت الباحثة الى جملة من النتائج تؤشر اغلبھا احتواء عروض المسرح المدرسي على جملة من المفاھیم التربویة والثقافیة والاخلاقیة والفنیة وتاثیرھا على سلوك التلامیذ وتوصلت الى مجموعة من الاستنتاجات لخصت بعدة نقاط ومن ثم المقترحات والتوصیات التي تراھا ضروریة وختم بقائمة من المصادر. Directorial vision of the values of artistic and educational offerings in theater school in Diyala province By Suhad rasheed ali Master's Student/ Basic Education College / University Of Diyala Abstract The theatre has an active role in establishing the artistic and educational concepts and it is considered one of the rational and artistic communitive tools in a useful ways because it is an effective tool for child imagination in flexible way. The problem of the research list in the directive vision of artistic and educational values, the mechanisms of communicating the educational values and making the child familiar with art and developing his artistic taste ; this reach is built on this basis which includes four chapters . The first chapter talks about the research problem which is summarized with the following question: What is the directive vision for the artistic and educational in school educational concepts and it is considered one of the rational and artistic communative tools in a useful ways because it is an effective tool for child imagination in flexible way. The problem of the research list in the directive vision of artistic and educational values,the mechanisms of communicating the educational values and making the child familiar with art and developing his artistic taste ; this reach is built on this basis which includes four chapters . The first chapter talks about the studies and the signs of the theoretical frame. The third chapter is about displaying the research procedures within describing the research society which contented a collection of theatre shows for primary stage in diala province and contained the research samples which are (2) samples .The researcher depended on the signs of the theoretical frame in analyzing the research samples. In the fourth chapter . the researcher has concluded a number of results . which most of them point out that the school theatre shows contain a group conclusions and made a summary of many points and then the proposals and recommendations which the researcher sees the necessary and finished the research with a list of reference